2002
DOI: 10.1677/erc.0.0090045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms implicated in the growth regulatory effects of vitamin D in breast cancer.

Abstract: It is now well established that, in addition to its central role in the maintenance of extracellular calcium levels and bone mineralization, 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ), the active form of vitamin D, also acts as a modulator of cell growth and differentiation in a number of cell types, including breast cancer cells. The anti-proliferative effects of 1,25(OH) 2 D 3 have been linked to suppression of growth stimulatory signals and potentiation of growth inhibitory signals, which lead to changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
183
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(196 citation statements)
references
References 88 publications
8
183
1
4
Order By: Relevance
“…On the other hand, it is well established that active vitamin D metabolites or analogs are efficacious in inhibiting cell proliferation and inducing cell differentiation [26][27][28][29]. Here we use an unique mouse mammary organ culture system to demonstrate the chemopreventive role of 25(OH)D 3 in DMBA-induced carcinogenesis of mouse mammary glands at its physiological concentration.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is well established that active vitamin D metabolites or analogs are efficacious in inhibiting cell proliferation and inducing cell differentiation [26][27][28][29]. Here we use an unique mouse mammary organ culture system to demonstrate the chemopreventive role of 25(OH)D 3 in DMBA-induced carcinogenesis of mouse mammary glands at its physiological concentration.…”
Section: Discussionmentioning
confidence: 99%
“…the known anticarcinogenic effects of vitamin D with regard to apoptosis, cell differentiation and proliferation and growth inhibition of human mammary epithelial cells by both 1,25(OH) 2 29,30 Confirming our a priori hypothesis, we observed in this population-based case-control study a significantly inverse association between Conditional logistic regression stratified by age and adjusted for time of blood collection.-2 Conditional logistic regression stratified by age and adjusted for time of blood collection, number of births, first-degree family history, age at menarche, duration of breast-feeding, BMI, alcohol consumption. plasma 25(OH)D and premenopausal breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Most of the epidemiologic studies regarding breast cancer risk have assessed the effects of vitamin D only for dietary intake yielding inconsistent results. [7][8][9][10][11][12][13][14][15] However, beside dietary intake, the main source of vitamin D is cutaneous production via sun exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1α 25(OH) 2 D 3 also induced apoptosis through directly activate caspase effector molecules, although it is unclear whether 1, 25(OH) 2 D 3 -induced apoptosis is caspase-dependent or independent (Deeb et al, 2007). It has also reported that some breast cancer cells shows potentiate TNF alpha induced apoptosis through the death receptor pathway, which is linked to the activation of caspases and phospholipase A2 (Colston and Hansen, 2002). A novel mechanism of 1α 25(OH) 2 D 3 -mediated apoptosis in epithelial ovarian cancer cells was proposed by Jiang et al(2004), wherein they showed that 1 α 25(OH) 2 D 3 destabilizes telomerase reverse transcriptase (TERT) mRNA, therefore inducing apoptosis through telomere attrition resulting from the down-regulation of telomerase activity and it is first study which demonstrate stability of hTERT mRNA by a hormone.…”
Section: Cyp24a1mentioning
confidence: 99%